2013
DOI: 10.1177/0892705713503669
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and compatibility of poly(4-methyl-1-pentene) and polypropylene in their blends

Abstract: Isotactic poly(4-methyl-1-pentene) (PMP) is a semicrystalline polyolefin with many unique properties. The crystallization theory of pure PMP had been well studied based on its molecular structure. In this study, the crystallization behavior and compatibility of PMP/polypropylene (PP) blends were investigated by differential scanning calorimetry, x-ray diffraction, scanning electron microscopy (SEM), and mechanical testing. It was found that the PP crystallization behavior was strongly affected by the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In our previous study on PMP/polypropylene (PP) blends, we have found that PMP and PP have a good compatibility. 11 There was no obvious phaseseparated morphology on the notched impact cross section of PMP/PP blend. Due to the similar molecular chains structure and the good compatibility of PMP and PP, we took the toughening modification of PP as reference to modify PMP with various thermoplastic elastomers.…”
Section: Introductionmentioning
confidence: 92%
“…In our previous study on PMP/polypropylene (PP) blends, we have found that PMP and PP have a good compatibility. 11 There was no obvious phaseseparated morphology on the notched impact cross section of PMP/PP blend. Due to the similar molecular chains structure and the good compatibility of PMP and PP, we took the toughening modification of PP as reference to modify PMP with various thermoplastic elastomers.…”
Section: Introductionmentioning
confidence: 92%